The metabolic capacity of lipid droplet localized acyl-CoA synthetase 3 is not sufficient to support local triglyceride synthesis independent of the endoplasmic reticulum in A431 cells - Poppelreuther, Margarete; Sander, Simone; Domschke, Susanne Karolin Sabine; Ehehalt, Robert; Stremmel, Wolfgang; Füllekrug, Joachim (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2018)
ACSL3 is the only long chain fatty acyl-CoA synthetase consistently found on growing and mature lipid droplets (LDs), suggesting that this specific localization has biological relevance. Current models for LD growth propose that triglycerides are synthesized by enzymes at the LD surface, with activated fatty acids provided by LD localized ACSL3, thus allowing growth independent of the ER. Here, we tested this hypothesis by quantifying ACSL3 on LDs from human A431 cells. RNAi of ACSL3 reduced the oleoyl-CoA synthetase activity by 83%, suggesting that ACSL3 is by far the dominant enzyme of A431 cells. Molar quantification revealed that there are 1.4 million ACSL3 molecules within a single cell. Metabolic labeling indicated that each ACSL3 molecule contributed a net gain of 3.1 oleoyl-CoA/s. 3D reconstruction of confocal images demonstrated that 530 individual lipid droplets were present in an average oleate fed A431 cell. A representative single lipid droplet with a diameter of 0.66μm contained 680 ACSL3 molecules on the surface. Subcellular fractionation showed that at least 68% of ACSL3 remain at the ER even during extensive fatty acid supplementation. High resolution single molecule microscopy confirmed the abundance of cytoplasmic ACSL3 outside of LDs. Model calculations for triglyceride synthesis using only LD localized ACSL3 gave significant slower growth of LDs as observed experimentally. In conclusion, although ACSL3 is an abundant enzyme on A431 LDs, the metabolic capacity is not sufficient to account for LD growth solely by the local synthesis of triglycerides.
Gesehen am 08.05.2020